On the Varying Effectiveness of Computer/Mobile-Assisted Language Learning - Ben-Itzhak, Svetla (International journal of education and development using information and communication technology, 2021)
Educational technology has evolved tremendously over the past fifty years. Computer- and mobile-assisted tools have enabled language learning to take place anytime and anyplace. This paper examines the effectiveness of computer/mobile-assisted language learning (C/MALL) by reviewing findings as reported in the literature and by discussing benefits as well as issues linked with using technology in second/foreign (L2) language education. Overall, despite reports that technology has enhanced language instruction and acquisition, some find that it has not been as effective as anticipated or may have even impeded learning. This paper argues that the deciding factor defining the depth and breadth of technology's effectiveness, in and outside of the classroom, is the teacher. Good teachers must precede technology for it to be effective in language learning. To improve the likelihood of effectively employing technology, this paper outlines key questions for teachers to consider when deciding whether to include technology in language instruction.